Ephesians and Artemis : the influence of the religious climate of western Asia Minor of the first century AD on the content and terminology of Paul’s prayer in Ephesians 1:15-23 - Visagie, Andre Jacobus (Stellenbosch : Stellenbosch University, 2010)
Thesis (MTh (Old and New Testament))--Stellenbosch University, 2010.